The disproportionate economic burden associated with severe and complicated obesity: a systematic review. Issue 11 (16th July 2013) - Grieve, E.; Fenwick, E.; Yang, H‐C.; Lean, M.
Summary: Burden of disease studies typically classify individuals with a body mass index (BMI) ≥ 30 kg m −2 as a single group ('obese') and make comparisons to those with lower BMIs. Here, we review the literature on the additional economic burden associated with severe obesity or classes 3 and 4 obesity (BMI ≥ 40 kg m −2 ), the fastest growing category of obesity, with the aim of exploring and disaggregating differences in resource use as BMI increases beyond 40 kg m −2 . We recognize the importance of comparing classes 3 and 4 obesity to less severe obesity (classes 1 and 2) as well as quantifying the single sub‐class impacts (classes 3 and 4). Although the latter analysis is the aim of this review, we include results, where found in the literature, for movement between the recognized subclasses and within classes 3 and 4 obesity. Articles presenting data on the economic burden associated with severe obesity were identified from a search of Ovid MEDLINE, EMBASE, EBSCO CINAHL and Cochrane Library databases. Data were extracted on the direct costs, productivity costs and resource use associated with severe obesity along with estimates of the multiplier effects associated with increasing BMI. Fifteen studies were identified, of which four disaggregated resource use for BMI ≥ 40 kg m −2 . The multiplier effects derived for a variety of different types of costs incurred by the severely obese compared with those of normal weight (18.5 kg m −2 < BMI < 25 kg m −2 ) ranged from 1.5 to 3.9 for direct costs, and from 1.7 to 8.0 for productivity costs. There are few published data on the economic burden of obesity disaggregated by BMI ≥ 40 kg m −2 . By grouping people homogenously above a threshold of BMI 40 kg m −2, the multiplier effects for those at the highest end of the spectrum are likely to be underestimated. This will, in turn, impact on the estimates of cost‐effectiveness for interventions and policies aimed at the severely obese.